2017
DOI: 10.1016/j.tele.2016.04.009
|View full text |Cite
|
Sign up to set email alerts
|

Love me Tinder: Untangling emerging adults’ motivations for using the dating application Tinder

Abstract: Although the smartphone application Tinder is increasingly popular among emerging adults, no empirical study has yet investigated why emerging adults use Tinder. Therefore, we aimed to identify the primary motivations of emerging adults to use Tinder. The study was conducted among Dutch 18-30 year old emerging adults who completed an online survey.Over half of the sample were current or former Tinder users (n = 163). An exploratory factor analysis, using a parallel analysis approach, uncovered six motivations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
281
3
31

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 319 publications
(333 citation statements)
references
References 62 publications
18
281
3
31
Order By: Relevance
“…For example, love, casual sex, and communication motives appeared to be more important among older participants. Men had higher mean scores on casual sex, ease of communication, and thrill of excitement motives in comparison with women (Sumter, Vandenbosch, & Ligtenberg, ). A recent mixed‐methods study found that users matched with those they were searching on Tinder less than half the time while using Tinder and the primary reasons for swiping either right or left (match vs. nonmatch) included attraction (the physical appearance of the other), being a selective swiper (being picky about approving a potential match), and interesting (similar interests and appeal of their posted bio).…”
Section: Romantic Relationships and Sexual Activity In Adolescence Anmentioning
confidence: 99%
“…For example, love, casual sex, and communication motives appeared to be more important among older participants. Men had higher mean scores on casual sex, ease of communication, and thrill of excitement motives in comparison with women (Sumter, Vandenbosch, & Ligtenberg, ). A recent mixed‐methods study found that users matched with those they were searching on Tinder less than half the time while using Tinder and the primary reasons for swiping either right or left (match vs. nonmatch) included attraction (the physical appearance of the other), being a selective swiper (being picky about approving a potential match), and interesting (similar interests and appeal of their posted bio).…”
Section: Romantic Relationships and Sexual Activity In Adolescence Anmentioning
confidence: 99%
“…As such, I utilize popular press articles in addition to sparse empirical studies to define Tinder practices. Until recently, there has been minimal empirical research (e.g., Ansari & Klinenberg, 2015;David & Cambre, 2016;Duguay, 2016;Sumter, Vandenbosch, & Lighenberg, 2017; Ward, 2016) that examined Tinder's interpersonal relationship initiation processes.The traditional relationship development model (Knapp & Vangelisti, 2010) yields a descriptive dual staircase model for understanding relationship initiation and dissolution behaviors and patterns in face-to-face applications. The dual staircase involves partners navigating steps to escalation (i.e., coming together or initiation) and de-escalation (i.e., coming apart or dissolution).…”
mentioning
confidence: 99%
“…Even processes that necessarily include humans in the loop can be disintermediated to focus on the efficiency of the basic input-output. A romance, which in the nineteenth century could be spun out to cover several hundred pages of a novel, can now be shortcircuited from discovery to consummation into an evening using a dating app such as Tinder (Sumter et al 2017). The game of roulette used to involve an elaborate set of rituals in a casino which had the effect of slowing down the game and making it into a social event (stimulating the imaginations of authors such as Dostoyevsky, George Eliot and Ian Fleming).…”
Section: The Temporal Dimensionmentioning
confidence: 99%